Longmire defense - Johnson, Craig 1961- (New York Viking, 2023)
"Walt Longmire faces one of his most challenging crime scenes as he tries to reckon with the revelations of his last case where he confronted the ghosts of his past and questioned the very nature of justice and mercy in the hard country of the West. Deep in the heart of the Wyoming countryside, Sheriff of Absaroka County, Walt Longmire, is called to a crime scene like few others that he has seen. This crime brings up issues that go back to Walt's grandfather's time in Wyoming, as the revelations he learns about his grandfather come back to offer clues and motives for Walt's investigation. Filled with back-country action, and with the great cast of characters that readers have come to love with the Longmire series, this new book will be sure to satisfy both long-time readers and those new to the series"--
Deep in the heart of the Wyoming countryside, Sheriff Walt Longmire is called to a crime scene like few others that he has seen. This crime brings up issues that go back to Walt's grandfather's time in Wyoming: the 1940s murder of an accountant. The weapon, a rifle, was never found. As the revelations he learns about his grandfather come back to offer clues and motives for Walt's investigation, he is pushed to his ethical boundaries: the rifle is found-- and belonged to Lloyd Longmire. -- adapted from jacket
Series numeration from www.goodreads.com.
Sequel to: Hell and back.
112246
Keywords: Longmire, Walt -- (Fictitious character) -- Fiction; Sheriffs -- Fiction; Family secrets -- Fiction; Grandfathers -- Fiction; Cold cases (Criminal investigation) -- Fiction; Wyoming -- Fiction; Detective and mystery fiction; Fiction; Mystery fiction; Psychological fiction; Detective and mystery fiction